Analisis Yuridis Pengurangan Hukuman oleh Hakim Mahkamah Agung dalam Perkara Tindak Pidana Korupsi di Indonesia - Fauzia Rahawarin; Syah Awaluddin; Ridwan Fauzi Lestaluhu; Nur Patima Sangadji; Astriyanti La Uma; Zulhairin Ode Yoni; Ade Riski Rumain (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This paper examines the considerations of Supreme Court (MA) judges in reducing sentences for defendants of corruption crimes in Indonesia. The problem in this paper is what are the considerations of Supreme Court judges in reducing sentences for defendants of corruption crimes juridically. This research uses a juridical method by analyzing relevant theories, concepts, and laws and regulations. The results show that the judge's consideration is based on the good character of the defendant, the social impact, and the facts of the trial, referring to Law Number 48 of 2009 and Law Number 8 of 1981. Edhy Prabowo's case shows that the sentence reduction does not reflect public justice, on the contrary, Idrus Marham's case shows weakness due to the sentence reduction received.